MICROPOLARIZATION IN THE TREATMENT OF ACUTELY DEVELOPED VERTIGO - E. V. Shevchenko; D. V. Baymuratova; G. R. Ramazanov; S. S. Petrikov (Неотложная медицинская помощь)
Background Vertigo is the most common complaints addressed to a neurologist. There is few information about a role of physiotherapy in the treatment of vertigo.Objective: To assess an efficacy of stimulation current physiotherapy in the treatment of acutely developed vertigo.Material and methods. We examined 44 patients with a single or leading complaint of vertigo. Patients were randomized into two groups. Patients of the test group (22) underwent 2–6 procedures of micropolarization with the «emtc 12-01» device (russia) (4 procedures averagely), and patients of the control group (22) underwent 2–7 procedures simulating microcurrent physiotherapy (placebo) (4 procedures averagely). To assess the outcome of the treatment, all patients were tested on the eev scale (the european evaluation of vertigo) 1 hour prior to the first procedure and immediately after the last one.Results The initial intensity of vertigo in patients of the test group was higher than in patients of the comparison group (eev 12.4±3.0 and 9.7±2.6 points, respectively (p<0.05)). After the treatment, the results according to eev scale were 4.9±4.4 points (p<0.001 when compared with baseline values) in the test group and 7.8±3.1 points (p<0.05 when compared with baseline values) in the comparison group. The average difference between the eev assessment before and after treatment was significantly higher in the test group (7.5 points (99% ci=4.9-10.1)) than in the comparison group (1.7 points (99% ci=0.2-3.6)) (p<0.01).In both groups, subgroups of neurological and ent diseases were selected. Differences in the efficacy of treatment in patients between subgroups were not found. The mean difference between the eev assessment before and after treatment was 6.2 (95% ci=3.8-8.6) in patients with neurological diseases and 8.6 points (95% ci=5.5-11.6) in the subgroup of ent diseases; in the comparison group, the difference was 2.1 points (95% ci=-1.0-5.2) and 1.6 (95% ci=-0.5-3.7), respectively.Conclusion Microcurrent physiotherapy is an effective method of treatment for acute vertigo, and allows to reduce its severity significantly.